1991
DOI: 10.1115/1.2906271
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Heat Power Cycles for Specified Boundary Conditions

Abstract: Optimization of the power output of Carnot and closed Brayton cycles is considered for both finite and infinite thermal capacitance rates of the external fluid streams. The method of Lagrange multipliers is used to solve for working fluid temperatures that yield maximum power. Analytical expressions for the maximum power and the cycle efficiency at maximum power are obtained. A comparison of the maximum power from the two cycles for the same boundary conditions, i.e., the same heat source/sink inlet temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(76 citation statements)
references
References 0 publications
1
69
0
3
Order By: Relevance
“…Later, Ondrechen et al [16] determined the power generation limit from a finite hot temperature reservoir and an isothermal cold temperature reservoir using an infinite number of parallel Carnot cycles. Ibrahim et al [17] and Park and Min [18] employed a similar approach to determine numerically the maximum theoretical efficiency for a system with both a finite hot temperature reservoir and a finite cold temperature reservoir. These methods did not consider power generation from multiple heat sources.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Ondrechen et al [16] determined the power generation limit from a finite hot temperature reservoir and an isothermal cold temperature reservoir using an infinite number of parallel Carnot cycles. Ibrahim et al [17] and Park and Min [18] employed a similar approach to determine numerically the maximum theoretical efficiency for a system with both a finite hot temperature reservoir and a finite cold temperature reservoir. These methods did not consider power generation from multiple heat sources.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly-used way to account for the internal irreversibility of a machine (converter) is to introduce a cycle irreversibility ratio I according to [31] :…”
Section: Irreversibility Ratio Methodsmentioning
confidence: 99%
“…[5] showed that the production rate of entropy is greatly reduced by costing part of output power, when the optimum thermal efficiency is approximated as the average of the respective efficiency suggested by Carnot and that suggested by Curzon and Ahlborn [2]. In 1991, Ibrahim et al [6] considered irreversible parameters -the isentropic ratio of the isothermal processes and thus optimized the Carnot cycle by a more practical manner. Based on the assumption that the temperature of a gas varies linearly with the temperature of the surface of the wall of the cylinder that contains it, Klein [7] proposed the net output power and an optimized compression ratio for designing an engine with the greatest possible power output.…”
Section: Introductionmentioning
confidence: 99%